Annual report 2017: CGIAR Research Program on Forests, Trees and Agroforestry - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2018)
FTA contributes to 9 Sustainable Development Goals (SDGs), to all CGIAR Intermediate Development Outcomes (IDOs) and to 31 sub-IDOs with different levels of investment. With efforts targeted respectively at 29%, 33%, 38% across System Level Outcomes (SLOs) 1, 2 and 3, FTA balanced its work across four main production systems (natural forests, plantations, pastures and cropping systems with trees) dealing with a number of globally traded and/or locally important tree-crop commodities (timber, oil palm, rubber, coffee, cocoa, coconut, wood fuel, fruits, etc.), that form the basis for the livelihoods of hundreds of millions of smallholders.1 These commodities also represent an important share of the land area, including 13 million km2 of forests and 9.5 million km2 of agricultural lands (45% of the total agricultural area with >10% tree cover).